1998
DOI: 10.4141/p97-151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of method, rate and time of application of nitrogen fertilizer on seed production of tall fescue

Abstract: Fairey, N. A. and Lefkovitch, L. P. 1998. Effects of method, rate and time of application of nitrogen fertilizer on seed production of tall fescue. Can. J. Plant Sci. 78: 453-458. The production of seed of tall fescue (Festuca arundinacea Schreber) provides an opportunity to diversify the agriculture of the Peace region with a new, un-subsidized, soil-conserving, cash-crop. Nitrogen fertility and nutrition are major components of the production of any grass-seed crop. A field study was conducted on the nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…An additional 100 kg ha -1 of ammonium nitrate fertilizer (34-0-0) was broadcast on each tall fescue plot immediately after the PHM treatments were applied in August 1996 and 1997, in accordance with its known annual requirement (Fairey and Lefkovitch 1998). Also, as Midnight Kentucky bluegrass is susceptible to powdery mildew (Erysiphe graminis), each plot seeded to this grass was sprayed with a prophylactic application of 500 mL ha -1 Tilt (250 g L -1 propiconazole); in each harvest year, applications were made in early May (to the early-spring vegetative growth), in early-to-mid June, and in late August (to plots with PHM treatments where there was active vegetative growth).…”
Section: Methodsmentioning
confidence: 99%
“…An additional 100 kg ha -1 of ammonium nitrate fertilizer (34-0-0) was broadcast on each tall fescue plot immediately after the PHM treatments were applied in August 1996 and 1997, in accordance with its known annual requirement (Fairey and Lefkovitch 1998). Also, as Midnight Kentucky bluegrass is susceptible to powdery mildew (Erysiphe graminis), each plot seeded to this grass was sprayed with a prophylactic application of 500 mL ha -1 Tilt (250 g L -1 propiconazole); in each harvest year, applications were made in early May (to the early-spring vegetative growth), in early-to-mid June, and in late August (to plots with PHM treatments where there was active vegetative growth).…”
Section: Methodsmentioning
confidence: 99%
“…This study was the first in the Peace region to investigate the agronomic requirements of a tall fescue seed crop, and so the rate of N applied was based on recommendations for local seed crops of creeping red fescue. However, a recent study (Fairey and Lefkovitch 1998) has revealed that the N requirement of a tall fescue seed crop in the Peace region is in the range of 100 to 150 kg ha -1 , and similar to the maximum of 120 kg ha -1 N recommended in New Zealand (Hare and Rolston 1990).…”
Section: Discussionmentioning
confidence: 99%
“…at densities from 3.1 to 100 plants m -2 ), and at the three highest densities of 6.3, 12.5 and 25 plants m -2 with the 80-cm row spacing; reproductive tiller density ranged from 736 to 1483 m -2 . This current investigation was conducted with transplanted seedlings but, in a subsequent study on the nitrogen fertility responses of the same tall fescue cultivar, machine-drilled in 30 cm rows at 200 viable seeds m -2 , a reproductive tiller density in excess of 600 m -2 was found again, with treatment means all in the range 692 to 745 m -2 (Fairey and Lefkovitch 1998). Whether this capacity to support a greater density of reproductive tillers is controlled by the genetic constitution of the particular cultivar used for this study, by management factors, by environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations